Mechanisms underlying nickel nanoparticle induced reproductive toxicity and chemo-protective effects of vitamin C in male rats. (March 2019) - Kong, Lu; Hu, Wangcheng; Lu, Chuncheng; Cheng, Keping; Tang, Meng
Abstract: The purpose of this research is to go a step further study on the reproductive toxicities and the underlying mechanisms induced by nickel nanoparticles (NiNPs), and the possible protective action of vitamin C. Animal experiment was designed according to the one-generation reproductive toxicity standard, and rats were exposed to NiNPs through gavage. Ultrastructural, reactive oxygen species (ROS), oxidant and antioxidant enzymes, and cell apoptosis-related factors in the testicular tissue were analyzed. In contrast with the control group, the activity of surperoxide dismutase (SOD), catalase (CAT) and gonad-stimulating hormone (GSH) was reduced, while the content of nitric oxide (NO), malondialdehyde (MDA) and ROS was increased in the NiNPs treated animals. As the doses of NiNPs increase, the mRNA of apoptotic related factor Caspase-9, Caspase-8 and Caspase-3 showed an obviously upregulation. Protein expression of Bcl-2-associated X Protein (Bax) and apoptosis inducing factor (AIF) was significantly unregulated. After addition of antioxidants-vitamin C, the toxicity was reduced. Injured testicular tissue indicated that NiNPs exposure could damage the reproductive system. Our results suggest that NiNPs induce significant reproductive toxicities. The cellular apoptosis might be induced by caspase family proteinases, but the regulator factor (factor associated suicide (Fas), B-cell lymphoma-2 (Bcl-2), Bax, BH3-interacting domain death agonist (Bid) and AIF protein) might not be involved in this process. Thus, the mechanism of reproductive toxicity of NiNPs on rat testes involves in the induction of oxidative stress, which further results in cell apoptosis. Antioxidants-vitamin C shows a significant inhibition on the reproductive toxicities induced by NiNPs. Highlights: Nickel nanoparticles have induced testicular damage in adult male rats. Oxidative stress and apoptosis play an important role in reproductive toxicity induced by metallic nickel nanoparticles. The activity of antioxidative enzymes in rat testicular tissue is decreased by nickel nanoparticles. The activity of oxidative enzymes in rat testicular tissue is increased by nickel nanoparticles. Vitamin C as an antioxidant can antagonize the damage induced by nickel nanoparticles.